Reflections on the cultural dimension of language teaching - (:unkn) unknown (My University, 2005)
Both the objectives of the global approach and the fact that Turkey is facing European integration call for the implementation of concepts like ‘intercultural learning’ and ‘intercultural understanding’ in English language teaching. Although the cultural dimension of language is as important as its linguistic dimension, language education in Turkey mainly focuses on the latter. This study discusses the ideas and reflections of Turkish prospective teachers of English on the cultural dimension of language teaching.Çağ ımızın kü reselleşen dünya dü zeninde Avrupa ile bü tü nleşme sü recini yaşayan Tü rkiye'dekingilizce dil eğitiminde ‘kü ltü rlerarası öğrenme’ ve ‘kü ltü rlerarası anlama’ gibi kavramlar ön plana Çıkmıştır. Her ne kadar dilin kü ltü rel yönü dilbilgisel yönü kadar önemli olsa da, Tü rkiye'de dil eğitimi genellikle dilbilgisel yön ü zerine odaklanmıştır. BuÇalışmada Tü rkiye‘deki I˙ngilizce öğretmen adaylarıının dil eğ itiminin kü ltü rel yönüne ilişkin dü şü nce ve görü şleri ele alınmış, öğretmen adaylarının dil eğitiminin kü ltü rel yönüne nasıl yaklaştıkları ve bu yaklaşımların dil eğitimini nasıl etkilediğ i tartışılmıştır. © 2005 Taylor and Francis Group, LLC.
Keywords: Foreign language education; Intercultural learning; Teacher education